Increased risk of non-multiple sclerosis demyelinating syndromes in patients with preexisting septicaemia: a nationwide retrospective cohort study. Issue 1124 (17th June 2019) - Chou, Chung-Hsing; Lee, Jiunn-Tay; Tsai, Chia-Kuang; Lien, Li-Ming; Yin, Jiu-Haw; Lin, Chun-Chieh; Tsai, I-Ju; Sung, Yueh-Feng; Yang, Fu-Chi; Tsai, Chia-Lin; Wang, I-Kuan; Tseng, Chun-Hung; et al.
Abstract : Background: Growing evidence shows links between septicaemia and non-multiple sclerosis demyelinating syndromes (NMSDS); nevertheless, epidemiological data are still very limited. This study aimed to explore the relationship between septicaemia and NMSDS in a general population. Methods: The study included 482 781 individuals diagnosed with septicaemia and 1 892 825 age/sex-matched non-septicaemia patients for the comparison. Data were drawn from a population-based nationwide National Health Insurance Research Database Taiwan, from 1 January 2002 to 31 December 2011. The two cohorts of patients with and without septicaemia were followed up for the occurrence of NMSDS. The Cox-proportional hazard regression model was performed to estimate adjusted HR after multivariate adjustment. Results: Individuals with septicaemia had a 4.17-fold (95% CI 3.21 to 5.4, p < 0.001) higher risk to develop NMSDS compared with those without septicaemia. Patients aged <65 years had a greater NMSDS risk (<45 years: HR = 6.41, 95% CI 3.65 to 11.3, p < 0.001; 45–64 years: HR = 6.66, 95% CI 3.98 to 11.2, p < 0.001). Furthermore, females with septicaemia and individuals with higher severity of septicaemia were associated with increased risks of developing NMSDS. Conclusions: Our results indicated that patients with septicaemia were likely to develop NMSDS. A possible contributing role of septicaemia in increasing the hazard of NMSDS is proposed, based on the outcome that individuals with higher severity of septicaemia carried elevated threat of encountering NMSDS.